PROPAGACAO DE PSEUDOCISTOS DO PANCREAS PARA O FIGADO E BACO. RELATO DE DOIS CASOS - Quevedo, F. C.; Achilles, P.; De Franco, M. F. (My University, 1975)
Two autopsy cases of pancreatic pseudocystes are reported; case 1 involved perforation into the liver, and case 2, perforation into the spleen. In case 1, the pseudocyst was located in the caput, with drainage into the liver through the lesser omentum; secondary pseudocysts had developed in the liver, especially along the major portal tracts and there was laboratory evidence of obstructive jaundice. In case 2, the pseudocysts of the tail of the pancreas involved the spleen, and showed formation of secondary splenic pseudocysts; the clinical features and laboratory findings were typical of a primary chronic pancreatic disease. A review of the literature on the subject disclosed cases of spontaneous drainage of pancreatic pseudocysts into neighbouring hollow visceral organs, as well as internal drainage into the kidney.
Drainage of pancreatic pseudocysts into the liver and into the spleen. Report of 2 cases